Cost of disorders of the brain in Slovenia in 2010 - Jurij Bon (Zdravniški Vestnik, 2013)
Background: The spectrum of disorders of the brain is large, covering a wide range of neurological and psychiatric conditions. They have a high prevalence and cause short- and long-term impairments and disabilities, representing approximately one third of the whole disease burden in Western societies. In a European Brain Council (EBC) landmark study, the costs for 12 major groups of disorders of the brain in Europe in year 2004 were estimated for the first time. This estimate was limited in scope and conservative due to the lack of sufficiently comprehensive epidemiological and/or economic data on several important diagnostic groups. An updated EBC study on cost of disorders of the brain in Europe for 2010 covered 19 major groups of disorders with an increased range of age groups and more cost items. Revised estimates also included the new EU member states, and hence a population of 514 million people. Based on the same methodology, individual countries are now shaping their respective national cost estimates. Here we present the relevant data on estimated cost of brain disorders in Slovenia for 2010. Aims: To employ the EBC methodology to estimate the number of persons with defined disorders of the brain in Slovenia in 2010, the total cost per person related to individual disease in terms of direct and indirect costs, and an estimate of the total cost per disorder. Methods: The best available estimates of the prevalence and cost per person for 19 groups of disorders of the brain (covering well over 100 specific disorders) were identified via a systematic review of the published literature. The following range of mental and neurologic groups of disorders was covered: addictive disorders, affective disorders, anxiety disorders, brain tumors, childhood and adolescence disorders (developmental disorders), dementia, eating disorders, epilepsy, mental retardation, migraine, multiple sclerosis, neuromuscular disorders, Parkinson’s disease, personality disorders, psychotic disorders, sleep disorders, somatoform disorders, stroke, and traumatic brain injury. A cost model developed to combine the epidemiologic and economic data and estimate the total cost of each disorder in European countries was populated with national statistics from Eurostat to adjust all costs to 2010 values, converting all local currencies to Euro, imputing costs for countries where no data were available, and aggregating country estimates to purchasing power parity adjusted estimates for the total cost of disorders of the brain in Europe 2010.Results: The total cost of disorders of the brain for Slovenia is estimated at €2,425 billion in 2010, adjusted for purchasing power parities (€PPP). Direct costs constitute the majority of costs (42.3% direct healthcare costs and 22.0% direct non-medical costs) whereas the remaining 35.7% were indirect costs associated with patients’ production losses. On average, the estimated cost per person with a disorder of the brain in Slovenia ranged between €PPP 178 for headache and €PPP 2,2045 for neuromuscular disorders. The Slovenian per capita cost of disorders of the brain was €PPP 1,185. The cost (in million €PPP for 2010) of the disorders of the brain included in this study was as follows: mood disorders: 329.3; anxiety disorders: 289.4; stroke: 284.7; psychotic disorders: 277.3; dementia: 214.9; addiction: 195.0; mental retardation: 144.7; headache: 113.1; sleep disorders: 105.3; brain injury: 93.8; personality disorders: 79.1; childhood/adolescence disorders: 64.4; somatoform disorder: 62.7; multiple sclerosis: 57.7; Parkinson’s disease: 36.1; epilepsy: 35.8; neuromuscular disorders: 22.6; brain tumors: 16.4; eating disorders: 2.6. Conclusion: This EBC study is based on the best currently available data in Europe and the model enables extrapolation to countries where no data could be found. Still, the scarcity of data is an important source of uncertainty in estimates and may imply over- or underestimations in some disorders and countries, including Slovenia, where there are still no reliable epidemiological and health-economic data on brain disorders. Even though this review included many disorders, diagnoses, age groups and cost items that were omitted in 2004, there are still remaining disorders that could not be included due to limitations in the available data. The estimate of the total cost of brain disorders in Europe and Slovenia is therefore considered to be conservative. In terms of the health economic burden outlined in the EBC report and here, disorders of the brain likely constitute the number one economic challenge for health care in all European countries, now and in the future. The results are consistent with administrative data on the health care expenditure in Europe, and comparable to previous studies on the cost of specific disorders in Europe, while being lower than analogous estimates from the US. The reported results should be considered by all stakeholders, including policy makers, industry and patient advocacy groups, to reconsider the current science, research and public health agenda and shape a coordinated national action-plan to address the imminent challenges posed by disorders of the brain.